2021
DOI: 10.30560/sdr.v3n3p28
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Education to Meet the Global Demands: Industrial Inclusiveness in University Curriculum

Abstract: The world entered to knowledge-based economy which is based on the production and use of information. Today computer technology, language proficiency and logistics play a major role. University Curriculum connects the secondary level education and the industry. Therefore, industry inclusiveness is essential in transforming children to an industry worker or an entrepreneur. This paper is derived from an opinion survey, desk research, and a case study. Reports of international institutions were studied extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…A significant factor that influences students' decisions in choosing courses from the Humanities, Education, and Management (HEM) as their major is the availability of flexible payment options for degree programs. In addition, female students are more likely to choose undergraduate HEM programs, but women still struggle to get work (Edirisinghe et al, 2021). These facts revealed that Sri Lanka is lacking a proper system for students to select suitable higher education program.…”
Section: Introductionmentioning
confidence: 99%
“…A significant factor that influences students' decisions in choosing courses from the Humanities, Education, and Management (HEM) as their major is the availability of flexible payment options for degree programs. In addition, female students are more likely to choose undergraduate HEM programs, but women still struggle to get work (Edirisinghe et al, 2021). These facts revealed that Sri Lanka is lacking a proper system for students to select suitable higher education program.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Sri Lankan context, due to the capacity restraint in state sector, higher Education Institutes need for the participation in parallel system of private sector higher Education has emerged (Kelegama, 2017). Female students prefer Humanities, Education, Management (HEM) yet majority remain unemployed (Edirisinghe, et al, 2021). Secondary school graduates who cannot enter the state university as a consequence of limited capacity need option to continue their higher education dreams.…”
Section: Introductionmentioning
confidence: 99%
“…Computer technology and language proficiency are fundamental prerequisites in the knowledge economy. (Edirisinghe, et al, 2021). Therefore, it is required the longterm plans in Sri Lanka to increase the higher educational opportunities all over the country (Dona and Warusavitarana, 2014).…”
Section: Introductionmentioning
confidence: 99%